Tinjauan Naratif: Keselarasan Strategis pada Perencanaan Strategis TI berdasarkan Ward and Peppard - Maulana, Yoppy Mirza (Jurnal Manajemen Informatika JAMIKA, 2024)
IT Strategic Planning (ITSP) is a long-term IT development plan to support organizational goals. ITSP describes a business strategy in an organization by utilizing IT as a supporter in achieving organizational goals. One important factor in implementing ITSP is the use of a methodology for aligning business strategy and IT strategy (strategic alignment). One of the ITSP methodologies is Ward and Peppard which is a comprehensive ITSP framework to support strategic alignment (SA). SA in ITSP is an important requirement in achieving organizational success and is an important issue from a manager's perspective. Based on this, a narrative review research was conducted regarding the implementation of SA in PSTI based on Ward and Peppard. The results of this research explain the application of SA using the critical success factors (CSF) or Balanced Scorecard (BSC) method. The results of the description of the application of the CSF method were 58%, the BSC method was 17%, and the combination of the CSF and BSC methods was 25%. However, all research has not explained this relationship in SA. Therefore, for further research, SA should describe the relationship between goals, business strategy, targets, and measurements by determining SA based on CSF or BSC.